Impact of Labour-Management Relationship on Lecturersâ€™ Performance in Tertiary Institutions in Taraba State - Amaechi, Appolus Azunwanne; Obiweluozor, Nkechi (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
This paper examined the impact of labour-management relationship on lecturersâ€™ performance in tertiary institutions in Taraba State.  The researcher adopted the cross-sectional survey research design. The population of the study comprise of all the 4 tertiary institutions in the State with a staff strength of 3,214. The simple stratified random sampling technique was used to select a sample of 280 staff stratified along principal officers, academic, non-academic and union executives who participated in the research.  A 15-item researcher-developed questionnaire titled â€œLabour-Management Relationship Questionnaire (LMRQ)â€ was used as instrument for data collection. Three research questions and one null hypothesis guided the study. Data collected were analyzed using Mean, standard deviation and percentage scores. The Chi-Square statistic was used to test the null hypothesis at 0.05 level of significance. The findings revealed that unhealthy labour-management relationship negatively affect lecturersâ€™ performance in tertiary institutions in Taraba State. Conclusion was drawn and it was recommended that Administrators of tertiary institutions and government should endeavour to maintain cordial relationship with their labour force to enhance lecturersâ€™ productivity and or performance. Keywords:   Labour Union, management, Lecturersâ€™ performance, tertiary institution.